Insights into oral microbiome and colorectal cancer – on the way of searching new perspectives - Kudra, Anna; Muszyński, Damian; Sobocki, Bartosz Kamil; Atzeni, Alessandro; Carbone, Ludovico; Kaźmierczak-Siedlecka, Karolina; Połom, Karol; Kalinowski, Leszek (Frontiers in Cellular and Infection Microbiology, 2023)
Microbiome is a keystone polymicrobial community that coexist with human body in a beneficial relationship. These microorganisms enable the human body to maintain homeostasis and take part in mechanisms of defense against infection and in the absorption of nutrients. Even though microbiome is involved in physiologic processes that are beneficial to host health, it may also cause serious detrimental issues. Additionally, it has been proven that bacteria can migrate to other human body compartments and colonize them even although significant structural differences with the area of origin exist. Such migrations have been clearly observed when the causes of genesis and progression of colorectal cancer (CRC) have been investigated. It has been demonstrated that the oral microbiome is capable of penetrating into the large intestine and cause impairments leading to dysbiosis and stimulation of cancerogenic processes. The main actors of such events seem to be oral pathogenic bacteria belonging to the red and orange complex (regarding classification of bacteria in the context of periodontal diseases), such as Porphyromonas gingivalis and Fusobacterium nucleatum respectively, which are characterized by significant amount of cancerogenic virulence factors. Further examination of oral microbiome and its impact on CRC may be crucial on early detection of this disease and would allow its use as a precise non-invasive biomarker.